Gene duplication of coagulation factor V and origin of venom prothrombin activator in Pseudonaja textilis snake - Minh Le, Thi Nguyet; Reza, Md Abu; Swarup, Sanjay; Kini, R. Manjunatha (Thrombosis and Haemostasis, 2005)
The origin and evolution of venom toxins is a mystery that has evoked much interest. We have recently shown that pseutarin C, a prothrombin activator from Pseudonaja textilis venom, is structurally and functionally similar to mammalian coagulation factor Xa – factor Va complex. Its catalytic subunit is homologous to factor Xa while the nonenzymatic subunit is homologous to factor Va. P.textilis therefore has two parallel prothrombin activator systems: one expressed in its venom gland as a toxin and the other expressed in its liver and released into its plasma as a haemostatic factor. Here we report the complete amino acid sequence of factor V (FV) from its liver determined by cDNA cloning and sequencing. The liver FV shows 96% identity to pseutarin C nonenzymatic subunit. Most of the functional sites involved in its interaction with factor Xa and prothrombin are conserved. However, many potential sites of post-translational modifications and one critical cleavage site for activated protein C are different. The absence of the latter cleavage site makes pseutarin C nonenzymatic subunit resistant to inactivation and enhances its potential as an excellent toxin. By PCR and real-time quantitative analysis, we show that pseutarin C nonenzymatic subunit gene is expressed specifically in the venom gland at ~280 fold higher than that of FV gene in liver. These two are thus encoded by two separate genes that express in a highly tissue-specific manner. Our results imply that the gene encoding pseutarin C nonenzymatic subunit was derived by the duplication of plasma FV gene and they have evolved to perform distinct functions.
Keywords: Coagulation factor V; gene duplication; Pseudonaja textilis; venom toxin evolution